Deterministic Seismic Hazard Analysis (DSHA) and Peak Ground Acceleration Mapping in West Java (2018–2024) - Rayhan Irfan Hielmy (Yayasan Kita Menulis - JoCPES, 2025)
West Java is a region with one of the most complex tectonic settings in Indonesia, influenced by the Sunda Megathrust subduction zone and an active inland fault system. This study aimed to estimate the Peak Ground Acceleration (PGA) values in the West Java region using a Deterministic Seismic Hazard Analysis (DSHA) approach with the Maximum of Maxima criteria. The data used is sourced from the BMKG earthquake catalog for the 2018–2024 period, which includes the most recent epicenter, hypocenter depth, and magnitude parameters. PGA calculations were performed using the Milne attenuation model for each grid point in the target area, followed by spatial interpolation using PyGMT software. The analysis results reveal a significant bimodal seismic hazard characteristic. An absolute maximum PGA value of 0.46 g was identified, triggered by a local shallow crustal earthquake with a magnitude of M 5.8 at a shallow depth within the inland region. Meanwhile, the southern coastal zone is dominated by the influence of a large Megathrust earthquake (M 8.7), although its shaking impact attenuates as it moves inland toward northern population centers. These findings confirm that while subduction sources possess greater energy potential, local active inland faults pose a more direct and destructive shaking threat to densely populated inland areas. The hazard map generated in this study is expected to serve as a crucial technical reference for resilient infrastructure planning and the updating of earthquake mitigation strategies in West Java Province.